2013
DOI: 10.3389/fnins.2013.00252
|View full text |Cite
|
Sign up to set email alerts
|

Independent impacts of age and hearing loss on spatial release in a complex auditory environment

Abstract: Listeners in complex auditory environments can benefit from the ability to use a variety of spatial and spectrotemporal cues for sound source segregation. Probing these abilities is an essential part of gaining a more complete understanding of why listeners differ in navigating the auditory environment. Two fundamental processes that can impact the auditory systems of individual listeners are aging and hearing loss. One difficulty with uncovering the independent effects of age and hearing loss on spatial relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
154
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(177 citation statements)
references
References 38 publications
19
154
1
Order By: Relevance
“…However, the researchers did not examine release at smaller separations than 15 , or with older or HI listeners. One reason to examine the effects of small separations in older listeners in particular, is that Gallun et al (2013) showed that older individuals often achieve less SRM than younger individuals, regardless of hearing status. F€ ullgrabe et al (2015) concluded that reductions in SRM could be attributed to cognitive changes related to aging rather than age-related loss of binaural senstivity per se.…”
Section: Introductionmentioning
confidence: 99%
“…However, the researchers did not examine release at smaller separations than 15 , or with older or HI listeners. One reason to examine the effects of small separations in older listeners in particular, is that Gallun et al (2013) showed that older individuals often achieve less SRM than younger individuals, regardless of hearing status. F€ ullgrabe et al (2015) concluded that reductions in SRM could be attributed to cognitive changes related to aging rather than age-related loss of binaural senstivity per se.…”
Section: Introductionmentioning
confidence: 99%
“…The level of each component was adjusted based on the difference between the audiogram of the listener being tested and the audiogram of a comparison listener with 0 dB HL thresholds at each of the six octave frequencies, and then the six waveforms were summed. To estimate thresholds, the levels of the two masking sentences were adjusted relative to the level of the target sentence according to a progressive tracking algorithm which has been shown to be comparable to and more efficient than adaptive tracking (Gallun et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Head-related transfer functions (HRTFs) were used to position the target sentences at 0° azimuth and the maskers either colocated with the target or at ± 45° (Gallun et al 2013;Xie 2013). In the first experiment the target sentences were fixed at either 19.5 dB SL (low SL condition) or 39.5 dB SL (high SL condition) above each participant's speech reception threshold (SRT) in quiet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallun et al (2013) demonstrated that listeners could be categorized in terms of their ability to use spatial and spectrotemporal cues to separate competing speech streams. They showed that the factor of age substantially reduced spatial release from masking, supporting the hypothesis that aging, independent of an individual's hearing threshold, can result in changes in the cortical and/or subcortical structures essential for spatial hearing.…”
mentioning
confidence: 99%